2021
DOI: 10.21203/rs.3.rs-181370/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Change in Postprandial Level of Remnant Cholesterol After a Daily Breakfast in Chinese Patients With Hypertension

Abstract: Background: Hypertension(HBP) is usually accompanied by hypertriglyceridemia that represents the increased triglyceride-rich lipoproteins(TRLs) and their cholesterol content(i.e. remnant cholesterol, RC). According to the European Atherosclerosis Society(EAS), high RC(HRC) is defined as fasting RC ≥ 0.8mmol/L or/and postprandial RC ≥ 0.9mmol/L. However, little was known about postprandial change in RC level after a daily meal in Chinese patients with HBP. Methods: One hundred and thirty-five subjects, includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Several previous studies have reported a high level of plasma RC in normotensive subjects may predispose to the development of hypertension [27]. In turn, hypertensive patients had higher level of RC than those without hypertension [13]. Considering the closely relationship between hypertension, RC and CVD, our study focused on the combined effect of hypertension and RC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several previous studies have reported a high level of plasma RC in normotensive subjects may predispose to the development of hypertension [27]. In turn, hypertensive patients had higher level of RC than those without hypertension [13]. Considering the closely relationship between hypertension, RC and CVD, our study focused on the combined effect of hypertension and RC.…”
Section: Discussionmentioning
confidence: 99%
“…Despite lipoprotein(a) and low-density lipoprotein cholesterol (LDL-C) [7,8], remnant cholesterol (RC) has been shown to play an important role in the incidence of atherosclerotic CVD [9][10][11]. In recent years, several studies have found a significant association between hypertension and RC: increased RC was significantly associated with higher central systolic blood pressure and hypertensive patients had higher level of RC [12,13]. However, no previous study has specifically evaluated the cumulative effect of hypertension and RC on risk of CVD in the general population.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the small sample size, another cause for this phenomenon could be the difference in the time of blood lipid test. We previously found that levels of TG and RC began to rise at 2 h and peaked at 4 h after a daily meal in Chinese in patients with coronary heart disease and HBP [13,14]. For some patients who are used to a high-fat and high-calorie diet, the peak of TG level may be higher or later [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we reported that the non-fasting cut-off values to determine HTG and HRC were TG level 2.02 mmol/L [13] and RC level 0.87 mmol/L [14], respectively, in Chinese subjects.…”
Section: Cut-off Values To Determine Htg and Hrcmentioning
confidence: 99%
See 1 more Smart Citation